Sifat Alami Gramatika Indonesia: Sistem Partikel Linguistik, Fungsi Penataan Konseptual, dan Representasi Kognitif - Thafhan Muwaffaq; Arianty Visiaty (Ranah: Jurnal Kajian Bahasa, 2023)
Our article aims to characterize the conceptual architecture of Indonesian grammar theoretically through a cognitive semantic approach. In its implementation, we applied introspective reflection on language data in the form of sentences that have been collected into a corpus. Applying the Conceptual Structuring System (Talmy, 2000b), we introspected the semantic function of grammar elements and their coherence with lexical elements that constitute sentences. We propose that conceptualization in the Indonesian language relies on the system of pairing and connecting morphemes, or what will be regarded here as linguistic particles. In other words, a sentence is a composition of complex particles that externalizes the organization of ideas, thoughts, or concepts as a predication construed into cognitive representations in the form of event schemas. Furthermore, the conceptual organization expressed as predication configures conceptual meaning with respect to spatiotemporal domains. This article sheds light on the cognitive architecture that conceptualizes Indonesian grammar, contributing to a deeper understanding of its structural characteristics and the experience of language meaning-making.  AbstrakPenelitian ini bertujuan untuk mengkarakterisasikan arsitektur konseptual gramatika Indonesia secara teoretis melalui pendekatan semantik kognitif. Pada pelaksanaannya peneliti menerapkan refleksi introspektif atas data bahasa berupa kalimat yang telah dikumpulkan ke dalam korpus. Menerapkan Sistem Penataan Konseptual (Talmy, 2000b), peneliti mengintrospeksi fungsi semantik unsur gramatika dan kesinambungannya dengan unsur leksikal yang mengkonstitusikan kalimat. Peneliti memproposisikan konseptualisasi dalam bahasa Indonesia bertumpu pada sistem pemasangan dan penghubungan morfem atau apa yang akan disebut di sini sebagai partikel linguistik. Dalam kata lain, kalimat adalah susunan partikel kompleks yang mengeksternalisasikan organisasi ide, pikiran, atau konsep sebagai sebuah predikasi yang ditafsirkan ke dalam representasi kognitif berupa skema kejadian. Selanjutnya, organisasi konseptual yang dinyatakan sebagai predikasi mengkonfigurasi makna konseptual berdasarkan domain ruang dan waktu. Artikel ini mencerahkan arsitektur kognitif yang dikonseptualisasikan gramatika Indonesia, dalam cara yang mengkontribusikan pemahaman lebih dalam tentang karakteristik struktural dan pengalaman pemaknaan bahasa.